The comparative study of Nasopharyngeal Carcinoma incidence and mortality in Malaysia and Thailand: a systematic review - Nur Andriana Sufea Hanan,; Rosminah Mohamed,; Nur Syahmina Rasudin, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Nasopharyngeal Carcinoma (NPC) is characterized by a distinct geographical distribution and is particularly prevalent in East and Southeast Asia. For further studies and better planning in the future, it is vital to have knowledge about the ecological parameters, including incidence, mortality and so on. The objective of this study is to analyze the trend of incidence and mortality of nasopharyngeal carcinoma (NPC) cases over time in Malaysia and Thailand and to offer a comprehensive understanding of the epidemiological patterns of NPC in Malaysia and Thailand, considering both the unique characteristics and shared features of the disease in these two nations. A systematic review was conducted. We searched the literature databases of PubMed, MOH, IntechOpen, SpringerLink and UI Scholars Hub for empirical studies examining the prevalence of NPC cases in Malaysia and Thailand between 2010 and 2022, which were restricted to studies written in English. Nine studies were included, which are three retrospective studies, two ecological studies, three descriptive studies and one narrative review study. The studies show that the inconsistent pattern of NPC cases from 2012 to 2022 suggests that the incidence of NPC fluctuated in both countries throughout this time. Furthermore, it was discovered that Thailand’s mortality trend was erratic, exhibiting both rises and falls. Nonetheless, it was found that Malaysia’s mortality rate was steadily rising. This is aligned with the increase in mortality rates, particularly in the Southeast Asian region and how the Human Development Index (HDI) is involved in these studies.